Perception of Roles as Peer Educators in High Schools to Prevent Drug Abuse among Adolescents - Ira Nurmala1, Elisa Dwi Pertiwi1, Yuli Puspita Devi1, Muthmainnah1, Riris Diana R1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Adolescence is a transition period between childhood and adulthood, adolescent tends to have high curiosity and seek identity. Adolescent is a vulnerable group as a target for drug dealer. The objective of this study was to determine the perception of students in carrying out their duties as peer educators. This study used qualitative study approach with a case study design which intended to define the perceptions of the research subjects through in-depth interviews, observations, and also document studies. The students’ perception of their roles as peer educators such as a keeper of confidential informations, motivators, sources of information, and discussion partners. The conclusion was that the students who were selected as peer educators in their school environment had a positive perception of the application of the method to prevent drug abuse among their peers. Therefore, the application of peer educator method in high schools in North Surabaya can be used as a reference for other schools to implement peer educator method to their students.